ECHI DEL NUOVO MONDO NELLE BIBLIOTECHE NAPOLETANE TRA I SECOLI XVI E XVII. - Hazen, Ignacio Rodulfo (Mediterranea - Ricerche Storiche)
The Venetian Republic, the Roman Church and the early humanist circles have been traditionally regarded as the main custodians of information about the Americas in Early Modern Italy. Yet new private libraries inventories show that also the Kingdom of Naples was a major center of interest about the New World, on account of the southern intellectual background but also due to the Spanish influence. This article adresses both the aristocratic and the officeholding class libraries in late Sixteenth and early Seventeenth century Naples, pointing out the main evidences of American interest, and assessing the role of the cultural bonds inside the Catholic Monarchy.